Diabetes coverage in Australian newspapers (2013‐2017): A computer‐based linguistic analysis. (1st October 2019) - Bednarek, Monika; Carr, Georgia
Abstract: Issue addressed: This study analysed diabetes coverage in 12 Australian metropolitan/national newspapers over a period of 5 years (2013‐2017). It aimed to describe quantitative tendencies in diabetes coverage (amount of articles per newspaper and over time) and to identify potential discrepancies between diabetes coverage and societal prevalence of diabetes. The study addressed the following research questions, with a focus on language use: How frequent are mentions of different types of diabetes? How are people with diabetes referred to? How frequent and how distributed are mentions of Aboriginal and Torres Strait Islander people and matters? Methods: Data were collected in electronic format, manually classified and processed using a specialised software program, with a focus on quantitative analysis. Results: 577 articles were classified as news and 117 were classified as "non‐news." The Australian Financial Review published the fewest items, followed by the NT News, while the West Australian and the Advertiser published the most. References to "type 2" appear slightly more frequent and more distributed than to "type 1" diabetes. The labelling of people with the noun diabetic/s occurs in about a quarter of the dataset. References to Aboriginal and Torres Strait Islander people or matters appear to be extremely rare in the analysed dataset. Conclusions: Diabetes coverage does not fully align with incidence of diabetes among Australians, and problematic language practices such as the labelling of people as "diabetics" continue to occur. So what?: Given the agenda‐setting function of the news media, new strategies may be needed to change how Australian metropolitan and national newspapers cover diabetes, especially in relation to incorporating Aboriginal and Torres Strait Islander voices and perspectives. Summary: This study presents an overview of diabetes coverage in 12 Australian metropolitan and national newspapers over a period of 5 years (2013‐2017). It applies specialised computer software to analyse the amount of coverage and type of language used in such items, and uncovers key areas in need of improvement.